2015
DOI: 10.1021/ma501878n
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Structures of PMAA–PMMA Block Copolymers: Synthesis, Characterization, and Self-Consistent Field Computations

Abstract: Block copolymers composed of methacrylic acid (MAA) and methyl methacrylate (MMA) blocks are interesting candidates for replacing surfactants in emulsion polymerization methods. Here the synthesis and experimental characterization of well-defined PMAA–PMMA block copolymers made via RAFT polymerization are reported. It is shown that these block copolymers self-organize in water into micellar spherical or cylindrical structures or into highly size disperse structures (probably vesicles) in aqueous salt solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The SCF theory is a powerful tool enabling the description of the self-assembly of complex colloidal structures [49][50][51][52][53] based on the minimization of a mean-field free-energy functional, which requires the introduction of three parameters (see Table 1 for values) as input of the model: (i) the short-range interaction parameters (Flory-Huggins parameters χ) between segments of molecules, (ii) the relative dielectric permittivity (ε), and (iii) the valence (ν). The dielectric permittivity and the valence account for the electrostatic contributions, whereas the Flory-Huggins parameters are key for the formation and stability of the self-assembly colloids.…”
Section: Methodsmentioning
confidence: 99%
“…The SCF theory is a powerful tool enabling the description of the self-assembly of complex colloidal structures [49][50][51][52][53] based on the minimization of a mean-field free-energy functional, which requires the introduction of three parameters (see Table 1 for values) as input of the model: (i) the short-range interaction parameters (Flory-Huggins parameters χ) between segments of molecules, (ii) the relative dielectric permittivity (ε), and (iii) the valence (ν). The dielectric permittivity and the valence account for the electrostatic contributions, whereas the Flory-Huggins parameters are key for the formation and stability of the self-assembly colloids.…”
Section: Methodsmentioning
confidence: 99%
“…6 For thermodynamically controlled processes the morphology is determined by the macromolecular structure, the solution composition and the temperature. 7 There are several theoretical approaches 8 which can accurately predict the morphology of thermodynamically controlled block copolymer assemblies including self-consistent field (SCF) theory [9][10][11][12][13] and density functional theory (DFT). [14][15][16] Monte Carlo (MC) and (coarse grained) molecular dynamics simulations (MD) [17][18][19][20] can be performed to verify the theoretical results, 8 or study cases where theoretical approaches fail.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the vast majority of the literature published in this area investigates the design of amphiphilic block copolymer particles and the corresponding morphology, [13][14][15] or the use of preformed amphiphilic block copolymers as surfactants. [28][29][30][31][32] We, however, recently demonstrated that industrially relevant poly(vinyl chloride-co-methyl acrylate) latex particles (40 wt.% solids) incorporating less than 2 wt.% of hydrophilic poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), or poly(sodium styrene sulfonate) (PSSNa) synthesized by RAFT could be produced using this strategy and ultimately form transparent films. 33 The present paper describes the successful implementation of this strategy using watersoluble PMAA obtained by RAFT for the production of surfactant-free film-forming latex particles composed of methyl methacrylate (MMA), n-butyl acrylate (BA) and styrene (S), in a one-pot/two-step process exclusively conducted in water.…”
Section: Introductionmentioning
confidence: 99%